2016
DOI: 10.1371/journal.pone.0151302
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation and Clinical Outcomes in Patients with Acute Myocardial Infarction: A Retrospective Observational Study

Abstract: PurposePatients with acute myocardial infarction (AMI) and respiratory impairment may be treated with either invasive or non-invasive mechanical ventilation (MV). However, there has been little testing of non-invasive MV in the setting of AMI. Our objective was to evaluate the incidence and associated clinical outcomes of patients with AMI who were treated with non-invasive or invasive MV.MethodsThis was a retrospective observational study in which consecutive patients with AMI (n = 1610) were enrolled. The as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Previous studies have indicated that about 8% of patients with AMI required mechanical ventilation, and 3-4% of patients were treated with hemodialysis or other forms of renal replacement therapy [34, 35]. And the use of these interventions has been proved to be significantly associated with the poor survival of patients [35, 36], which is the same as our results.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have indicated that about 8% of patients with AMI required mechanical ventilation, and 3-4% of patients were treated with hemodialysis or other forms of renal replacement therapy [34, 35]. And the use of these interventions has been proved to be significantly associated with the poor survival of patients [35, 36], which is the same as our results.…”
Section: Discussionsupporting
confidence: 89%
“…Approximately 8% of patients with AMI require mechanical ventilation, and 3-4% of are treated with hemodialysis or other forms of renal replacement therapy. 33,34 The use of these interventions has been proved to be strongly associated with the poor survival of patients, 35 a finding similar to our results.…”
Section: Dovepresssupporting
confidence: 91%
“…Regarding hemodynamics, PCWP is usually higher than 15mm Hg, which leads to increased left ventricular lling pressure. Hence, CS patients are often associated with severe pulmonary edema (5,13).…”
Section: Discussionmentioning
confidence: 99%